Impact of Vancomycin-Associated Acute Kidney Injury on Patient Outcomes in MRSA Bacteremia. (4th October 2017) - Luther, Megan; Timbrook, Tristan; Lopes, Vrishali; Caffrey, Aisling; LaPlante, Kerry
Abstract: Background: Acute kidney injury (AKI) is a well-known adverse effect of vancomycin. Varying degrees and causes of AKI have demonstrated different effects on patient outcomes. Since AKI with vancomycin is typically reversible, we investigated how AKI associated with vancomycin therapy impacts patient mortality and time to discharge. Methods: Unique patients with methicillin-resistant Staphylococcus aureus (MRSA) bacteremia and who received at least one dose of vancomycin were identified in a national Veterans Affairs cohort from January 1, 2002 to October 14, 2015. Patients with a history of dialysis in the previous year and those with AKI on admission were excluded. AKI was defined according to RIFLE criteria, as an increase in serum creatinine (SCr) of 0.5 mg/dL or 1.5× from the admission SCr, on a day they received vancomycin. Patient characteristics including demographics and comorbidities defined by ICD9 codes were compared between groups. Effect estimates for inpatient mortality were determined with a backward stepwise logistic regression model in SAS 9.2. For patients without inpatient mortality, time to discharge was analyzed using Wilcoxon rank-sum test. Results: There were 7691 included patients with MRSA bacteremia, and 23.8% ( n = 1830) developed AKI during therapy. Mean age was 66.7 (±12) years and 97.8% ( n = 7525) were male. Patients with AKI were more likely to have congestive heart failure, diabetes, chronic kidney disease, and to be admitted to the intensive care unit (all P < 0.001). Overall inpatient mortality was 17.7% ( n = 1361). The crude odds of inpatient mortality were 67% higher in patients with AKI. In the adjusted model, AKI was an independent predictor of mortality (OR 1.19, 95% CI 1.02–1.40, P < 0.03). Median (IQR) time to discharge was 11 (6–19) days without AKI and 18 (11–31) days with AKI ( P < 0.0001). Conclusion: Vancomycin-associated AKI is associated with increased inpatient mortality and longer time to discharge. Further research is needed to compare clinical outcomes for other groups of patients, and to determine the impact of monitoring interventions to improve safety and decrease AKI. Disclosures: A. Caffrey, Merck: Grant Investigator, Grant recipient The Medicines Company: Grant Investigator, Grant recipient Pfizer: Grant Investigator, Grant recipient K. LaPlante, Merck: Grant Investigator, Grant recipient Pfizer: Grant Investigator, Grant recipient Cempra: Scientific Advisor, Consulting fee The Medicines Company: Grant Investigator, Grant recipient Allergan: Scientific Advisor, Consulting fee Bard/ Davol: Scientific Advisor, Consulting fee Ocean Spray: Grant Investigator and Scientific Advisor, Consulting fee and Grant recipient Zavante: Scientific Advisor, Consulting fee Achaogen: Scientific Advisor, Consulting fee